Navigating the paradox of connectivity and isolation: Impacts on digital nomads' psychological well-being - Maherian Farshbaf, Mahin (Graduate School, 2025)
The present study focuses on the paradoxical experience of digital nomads, who often grapple with deep feelings of isolation despite being constantly connected through digital technologies. As remote work becomes a normalized part of global labor culture, the digital nomad lifestyle, once considered niche, has rapidly gained popularity. This lifestyle promises freedom, flexibility, and autonomy, yet it also presents unique psychological challenges, particularly around social disconnection and mental well-being. Through a quantitative research approach, this study investigates how digital nomads manage the balance between digital connectivity and physical or emotional isolation, and how this balance influences their psychological health. Data was collected from 300 self-identified digital nomads using validated psychological and social measurement tools, including the Revised UCLA Loneliness Scale, Lubben Social Network Scale, Social Media Use Integration Scale, and the Warwick-Edinburgh Mental Well-being Scale. The goal was to examine key variables such as loneliness, perceived isolation, social network strength, and mental resilience in a mobile, technology-driven lifestyle. The research is structured around three core hypotheses: that digital nomads who actively manage their digital connectivity experience greater psychological well-being; that perceived isolation correlates negatively with mental health; and that digital engagement moderates the psychological effects of isolation. Results suggest that while digital tools help maintain a sense of social presence and professional continuity, they cannot fully substitute for in-person connections. Moreover, passive or excessive use of digital media can actually heighten feelings of loneliness. This study highlights the complex interplay between digital engagement and social disconnection and adds to the limited but growing body of literature on digital nomadism. It also offers practical insights for individuals, organizations, and policymakers seeking to support this expanding segment of the workforce. Ultimately, the findings underscore the need for intentional connectivity strategies and community-building efforts to ensure that remote work remains not only sustainable but also mentally and emotionally fulfilling.
Bağlantılı olmanın ve yalnızlığın paradoksunda yol almak: Dijital göçebelerin psikolojik iyilik hâline etkileri
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2025
Keywords: loneliness; yalnızlık; digital technology; dijital teknoloji